Papain-like and legumain-like proteases in rice: genome-wide identification, comprehensive gene feature characterization and expression analysis - Wang, Wei (BMC Plant Biol, 2018)
BACKGROUND: Papain-like and legumain-like proteases are proteolytic enzymes which play key roles in plant development, senescence and defense. The activities of proteases in both families could be inhibited by a group of small proteins called cystatin. Cystatin family genes have been well characterized both in tobacco and rice, suggesting their potential roles in seed development. However, their potential targets, papain-like and legumain-like proteases, have not been well characterized in plants, especially in rice, a model plant for cereal biology. RESULTS: Here, 33 papain-like and 5 legumain-like proteases have been identified in rice genome, respectively. Gene structure, distribution in rice chromosome, and evolutionary relationship to their counterparts in other plants have been well characterized. Comprehensive expression profile analysis revealed that two family genes display divergent expression pattern, which are regulated temporally and spatially during the process of seed development and germination. Our experiments also revealed that the expression of most genes in these two families is sensitively responsive to plant hormones and different abiotic stresses. CONCLUSIONS: Genome-wide identification and comprehensive gene expression pattern analysis of papain-like and legumain-like proteases in rice suggests their multiple and cooperative roles in seed development and response to environmental variations, which provides several useful cues for further in-depth study. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12870-018-1298-1) contains supplementary material, which is available to authorized users.